1999
DOI: 10.1007/s11661-999-0308-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and cyclic oxidation behavior of a (Ni, Pt) Al coating on a desulfurized Ni-base superalloy

Abstract: The influences of sulfur impurities and Pt incorporation on the scale adhesion behavior of aluminide coatings were studied and compared. Low-sulfur NiAl coatings were prepared on a desulfurized, yttrium-free, single-crystal Ni-based superalloy by a modified version of a conventional aluminizing procedure based on chemical vapor deposition. The sulfur level in the resulting NiAl coatings was measured to be less than ϳ0.5 ppmw by glow-discharge mass spectroscopy. Platinum-modified aluminide coatings were synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(62 citation statements)
references
References 28 publications
4
58
0
Order By: Relevance
“…These results Current aluminide bond coats often contain Pt, which is now commonly added in conjunction with a low activity CVD aluminization process which results in a single phase β-(Ni,Pt)Al coating. [9] The role of Pt in oxidation has not been fully explained but it is clear from recent results on both cast aluminides [10] and CVD aluminide coatings [2] that Pt improves alumina scale adhesion. This beneficial effect is shown at 1100°C for cast aluminides, Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These results Current aluminide bond coats often contain Pt, which is now commonly added in conjunction with a low activity CVD aluminization process which results in a single phase β-(Ni,Pt)Al coating. [9] The role of Pt in oxidation has not been fully explained but it is clear from recent results on both cast aluminides [10] and CVD aluminide coatings [2] that Pt improves alumina scale adhesion. This beneficial effect is shown at 1100°C for cast aluminides, Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…[13] The comparison of simple and Pt-modified CVD a l u m i n i d e coatings on René N5 also demonstrated that Pt did not (1) reduce the alumina scale growth rate, (2) alter the diffusion of heavy elements into the coating during deposition or oxidation, or (3) alter the coating Al content before or after oxidation. [2,13].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations